A Novel Hydroxamate-Based Compound WMJ-J-09 Causes Head and Neck Squamous Cell Carcinoma Cell Death via LKB1-AMPK-p38MAPK-p63-Survivin Cascade - Yen, Chia-Sheng; Choy, Cheuk-Sing; Huang, Wei-Jan; Huang, Shiu-Wen; Lai, Pin-Ye; Yu, Meng-Chieh; Shiue, Ching; Hsu, Ya-Fen; Hsu, Ming-Jen (Frontiers in Pharmacology, 2018)
Growing evidence shows that hydroxamate-based compounds exhibit broad-spectrum pharmacological properties including anti-tumor activity. However, the precise mechanisms underlying hydroxamate derivative-induced cancer cell death remains incomplete understood. In this study, we explored the anti-tumor mechanisms of a novel aliphatic hydroxamate-based compound, WMJ-J-09, in Fadu head and neck squamous cell carcinoma (HNSCC) cells. WMJ-J-09 induced G2/M cell cycle arrest and apoptosis in FaDu cells. These actions were associated with liver kinase B1 (LKB1), AMP-activated protein kinase (AMPK) and p38 mitogen-activated protein kinase (p38MAPK) activation, transcription factor p63 phosphorylation, as well as the modulation of p21 and survivin. LKB1-AMPK-p38MAPK signaling blockade reduced WMJ-J-09’s enhancing effects in inducing p63 phosphorylation, p21 elevation and survivin reduction. Moreover, WMJ-J-09 caused an increase in α-tubulin acetylation and interfered with microtubule assembly. Furthermore, WMJ-J-09 suppressed the growth of subcutaneous FaDu xenografts in vivo. Taken together, WMJ-J-09-induced FaDu cell death may involve LKB1-AMPK-p38MAPK-p63-survivin signaling cascade. HDACs inhibition and disruption of microtubule assembly may also contribute to WMJ-J-09’s actions in FaDu cells. This study suggests that WMJ-J-09 may be a potential lead compound and warrant the clinical development in the treatment of HNSCC.